Pendampingan Komunitas Produsen Kecap Skala Rumah Tangga di Kelurahan Putat Jaya Kecamatan Sawahan Kota Surabaya - Wiwik Handayani; Sulastri Irbayuni; Luky Susilowati (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
Today, efforts to build the entrepreneurship of society have begun to grow. Making Soy Sauce is an opportunity for home industry to increase the level of economy of the community. However, the obstacle faced by the community is the high price of soybeans and the condition of the people in the Putat Jaya village who do not have a fixed income and do not have the skills, so it is necessary to find another alternative to making the soy sauce. By using the Asset-Based Community Development (ABCD) method, this study aims to provide training assistance to make soy sauce using cheaper ingredients, but it still has high quality. As a result of this assistance, the community was given counseling and twice practice to makie soy sauce from the basic ingredients of coconut water. The training in making coconut water sauce was successfully carried out, and the residents of Putat Jaya village were able to make good quality of soy sauce with savory taste, so that the community was able to become a soy sauce producer with coconut water and have a community of soy sauce makers.